Kiblat Dan Kakbah Dalam Sejarah Perkembangan Fikih - Mutmainnah Mutmainnah (Universitas Cokroaminoto Yogyakarta, 2017)
A description of the history and fiqh of Qibla cannot be separated from the site of the Ka'bah in Mecca. From there it can be known the problems experienced by the ummah when facing the problem of the correct direction of prayer, especially from those who live far from the Ka'bah. Its history also confirms that as the science and its supporting technology are improving in account with fiqh terms, both are important steps to determine the accuracy of the Qibla direction.